"... sei er dir wie der Heide und der Zöllner": das pragmatische Potential von Mt 18,17 in seinem Kontext (Mt 18,15-20) - Langner, Cordula (Biblische Notizen, 2005)
Usually the verse Mt 18:17 “… let him be to you as a Gentile and a tax collector” is interpreted as a legitimate proof for the exclusion (excommunication) from the community or church. Based on the exegetical research of the verse in its context, the author comes to the conclusion that is rather a very precise instruction how to treat the “sinner”: instead of exclusion, the verse demands for a special way of care with the intention integrating the sinful “brother” into the community.